213 Association between age of SLE diagnosis and disease damage differs across racial/ethnic groups: results from the california lupus epidemiology study. (April 2019) - Trupin, Laura; Rush, Stephanie; Katz, Patricia; DallEra, Maria C; Yazdany, Jinoos
Abstract : Background: Earlier age of SLE onset is associated with greater disease damage, even after taking into account the effects of current age and disease duration. We sought to determine if this association was consistent across racial and ethnic groups, given the differences in disease severity among these groups. Methods: Data derive from the baseline visit of the California Lupus Epidemiology Study (CLUES), an ongoing cohort of patients in the San Francisco Bay Area with confirmed SLE diagnoses, drawn from a variety of clinical sources and prior SLE studies. Participants provided access to medical records and had a visit with a study physician in which clinical labs were drawn. Disease damage was measured using the SLICC/ACR Damage Index (SDI), calculated at the study visit. Age of diagnosis was ascertained by the study physician or from the medical records. Race/ethnicity (White, African American, Hispanic of any race, and Asian) and educational attainment (high school or less, some college, college graduate) were determined by patient report. Due to the small sample size, patients from other racial groups were excluded from this analysis (n=5). Using multiple linear regression, we estimated a model of SDI as a function of race/ethnicity and age of diagnosis, plus terms for interaction between the variables. The model controlled for sex, current age, and education. Results: Among 323 participants, 89% were female, 39% Asian, 11% African American, 22% Hispanic of any race, and 29% White. Mean age was 45±14; mean age at diagnosis 29±12. Nearly half of respondents had a college degree. SDI at the baseline study visit ranged from 0 to 10 points, mean 1.8±2.0; 70% of the cohort had SDI>0. The regression model showed strong evidence (p=0.01) for interaction of age of diagnosis with race/ethnicity. As seen in the figure 1, SDI scores in racial/ethnic minorities were much higher among those diagnosed at younger ages; this relationship was not seen among whites. Conclusions: In this multi-ethnic cohort of SLE patients, the association of diagnosis age and disease damage varied according to race/ethnicity, with whites diagnosed at younger ages accumulating less damage than those in other racial/ethnic groups diagnosed at comparable ages. Future research should examine if these differences are due to phenotypic differences among the groups, diagnostic delays, or other access to care issues. Funding Source(s): Centers for Disease Control and Prevention (U01 DP005120)